Bioenergy feasibility study - Berzasca, Romania - Hirvonen, Markus (ed.) (Karelia University of Applied Sciences, 2014)
Central and Eastern European Forest Information Service (KIEMET) is a project that produces information on forestry, forest sector business environment, wood supply, forest enterprises and bioenergy markets in the CEE countries (Estonia, Latvia, Lithuania, Poland, Czech Republic, Slovakia, Belarus, Ukraine and Romania). As a part of the KIEMET-project University of Eastern Finland, Finnish Forest Research Institute and Karelia University of Applied Sciences conducted a case study on the feasibility of centralized heat production from biomass in Berzasca commune in Romania. KIEMET-project was funded by the European Social Fund 2010-2012.